Person, Aktør, Rolle: Inter-personel udveksling, performativ præsens og det nye publikum - Eigtved, Michael (Peripeti, 2021)
Eigtved suggests a model for a dramaturgically based conceptualization of the participants in popular participatory tv shows like »Talent 2008« (the Danish version of »Britain’s got Talent«) where the roles ‘played’ by participants (including judges and spectators) are never stable but in constant flux.